Syi’r ‘Alā safḥi al-ahram Dalam Dīwān Aḥmad Syauqī (Kajian Semiotika Riffaterre) - M. Yusril Kholik; Nofi Fitria Indasari; Budi Ilham (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2024)
This poem consists of 31 stanzas, but the most popular of these stanzas are the last two stanzas. This poem is the work of Ahmad Syauqi. In this poem there are many expressions whose full meaning cannot be understood, because there are so many figurative forms of words. This research aims to describe the meaning contained in the syi'r 'Alā safḥi al-ahram with heuristic and hermeneutic reading as well as describing the matrices, models and hypograms in the syi'r 'Alā safḥi al-ahram. The research method used in this research is a descriptive qualitative research method. The approach used in this research is a semiotic approach, namely using Riffaterre's semiotic theory. The type of research used in this research is library research. The results of a heuristic and hermeneutic reading of the poem 'Alā safḥi al-ahram by Ahmad Syauqi are a description of 1. the beauty and majesty of the Egyptian pyramids, 2. Welcome and praise for Ameen Rihani, 3. Praise for the beauty of the Arabic language. The model in this poem, the first model is in the sentence لكِ كالمعابدِ روعةٌ قدسيَّةٌ وعليك روحانيَّةُ العُبَّاد, the second model states يا نجمَ سوريَّا ولستَ بأولٍ ماذا نمَت من نيِّرٍ وقَّادِ the last model إن الذي ملأ اللغاتِ مَحاسنًا جعلَ الجمالَ وسِرَّه في الضادِ. The matrix in this poem is a compliment. The hypogram in this poem is related to the verses of the Koran and the hadith of the Prophet Muhammad. narrated by Imam Thabrani and Baihaqi.